The greatest trades of all time : top traders making big profits from the Crash of 1929 to today - Veneziani, Vincent W., 1986- (Hoboken, N.J. : Wiley, 2011)
'How top traders made huge profits during the most momentous market events of the past century. Financial and commodity markets are characterized by periodic crashes and upside explosions. In retrospect, the reasons behind these abrupt movements often seem very clear, but generally few people understand what's happening at the time. Top traders and investors like George Soros or Jesse Livermore have stood apart from the crowd and capitalized on their unique insights to capture huge profits.Engaging and informative, The Greatest Trades of All Time chronicles how a select few traders anticipated market eruptions, from the 1929 stock market crash to the 2008 subprime mortgage meltdown, and positioned themselves to excel while a majority of others failed. Along the way, author Vincent Veneziani describes the economic and financial forces that led to each market cataclysm and how these?individuals perceived what was happening beforehand and why they decided to place big bets, often at great risk and in opposition to consensus opinion at the time. Traders discussed include George Soros, Jesse Livermore, Paul Tudor Jones, John Templeton, and John Paulson Provide contemporary traders and investors with insights on how great traders make great trades Offers insights on market forecasting, mass psychology, and the importance of personal conviction in trading At a time when many investors are looking to the past for answers to the future, this book brings important historical moments in the financial markets to life'--
Includes bibliographical references and index.
Keywords: Speculation -- History; Stocks -- History; Investors -- History; Business cycles -- History